Effectiveness of Interstitial Laser Acupuncture Depends upon Dosage: Experimental Results from Electrocardiographic and Electrocorticographic Recordings - He, Wei (Hindawi Publishing Corporation, 2013)
The purpose of this study was to evaluate the influence of the duration of interstitial laser acupuncture therapy effects on neurovegetative and neurobioelectrical parameters like heart rate (HR), heart rate variability (HRV), and electroencephalogram (EEG). We investigated 6 male Sprague-Dawley rats. They underwent 10 min, 20 min, and 30 min interstitial laser acupuncture (in randomized order, with a break of at least 30 min between the different measurement conditions) at the acupoint Neiguan. HR changed significantly only during 20 min red laser stimulation, whereas 10 and 30 min stimulation did not induce significant changes. HRV did not change significantly during any of the different durations; however, an increase was found during 20 min irradiation. Neither the LF/HF ratio of HRV nor the integrated EEG showed significant changes. In this study, it could be experimentally proved that some effects of laser acupuncture are time dependent, and therefore the dosage, as well known from theory, also depends on the time factor. We could especially demonstrate that different treatment times lead to different effects on neurovegetative and neurobioelectrical parameters. Further studies are needed to verify or refute these results.